Differential efficacy of non-invasive vagus nerve stimulation for the acute treatment of episodic and chronic cluster headache: A meta-analysis. (July 2019) - de Coo, Ilse F; Marin, Juana CA; Silberstein, Stephen D; Friedman, Deborah I; Gaul, Charly; McClure, Candace K; Tyagi, Alok; Liebler, Eric; Tepper, Stewart J; Ferrari, Michel D; Goadsby, Peter J
Background: Two randomized, double-blind, sham-controlled trials (ACT1, ACT2) evaluated non-invasive vagus nerve stimulation (nVNS) as acute treatment for cluster headache. We analyzed pooled ACT1/ACT2 data to increase statistical power and gain insight into the differential efficacy of nVNS in episodic and chronic cluster headache. Methods: Data extracted from ACT1 and ACT2 were pooled using a fixed-effects model. Main outcome measures were the primary endpoints of each study. This was the proportion of participants whose first treated attack improved from moderate (2), severe (3), or very severe (4) pain intensity to mild (1) or nil (0) for ACT1 and the proportion of treated attacks whose pain intensity improved from 2–4 to 0 for ACT2. Results: The pooled population included 225 participants (episodic: n = 112; chronic: n = 113) from ACT1 (n = 133) and ACT2 (n = 92) in the nVNS (n = 108) and sham (n = 117) groups. Interaction was shown between treatment group and cluster headache subtype ( p  < 0.05). nVNS was superior to sham in episodic but not chronic cluster headache (both endpoints p  < 0.01). Only four patients discontinued the studies due to adverse events. Conclusions: nVNS is a well-tolerated and effective acute treatment for episodic cluster headache. Trial registration: The studies were registered at clinicaltrials.gov (ACT1: NCT01792817; ACT2: NCT01958125).